Synthesis of SF5-containing benzisoxazoles, quinolines, and quinazolines by the Davis reaction of nitro-(pentafluorosulfanyl)benzenes - Beier, Petr; Pastýříková, Tereza (Beilstein Journal of Organic Chemistry, 2013)
Meta- or para-nitro-(pentafluorosulfonyl)benzenes underwent the Davis reaction with arylacetonitriles to provide the SF5-containing benzisoxazoles. Good yields were obtained with arylacetonitriles containing the electron-neutral or electron-donor group, while those with the electron-acceptor group were found to be unreactive. Reductions of the benzisoxazoles gave ortho-aminobenzophenones in high yields. Their synthetic utility was demonstrated by condensation reactions with carbonyl compounds or amines to provide SF5-containing quinolines and quinazolines, respectively.
Keywords: benzisoxazoles; pentafluorosulfanyl group; quinazolines; quinolines; sulfurpentafluorides

The Nitro Group in Organic Synthesis - Ono, N. (Wiley & Sons, 2001)

(untitled) - Mąkosza, M. (Chem. Soc. Rev., 2010)

(untitled) - Mąkosza, M. (Synthesis, 2011)

(untitled) - Mąkosza, M.; Winiarski, J. (Acc. Chem. Res., 1987)

(untitled) - Mąkosza, M.; Wojciechowski, K. (Liebigs Ann./Recl., 1997)

(untitled) - Mąkosza, M.; Staliński, K. (Chem.–Eur. J., 1997)

(untitled) - Davis, R. B.; Pizzini, L. C. (J. Org. Chem., 1960)

(untitled) - Wróbel, Z.; Mąkosza, M. (Heterocycles, 1995)

(untitled) - Orlov, V. Y.; Sokovikov, Y. V.; Kotov, A. D.; Starikov, A. A. (Russ. J. Org. Chem., 2000)

(untitled) - Orlov, V. Y.; Kotov, A. D.; Bystryakova, E. B.; Kopeikin, V. V.; Mironov, G. S. (Zh. Org. Khim., 1994)

(untitled) - Davis, R. B.; Pizzini, L. C.; Benigni, J. D. (J. Am. Chem. Soc., 1960)

(untitled) - Sheppard, W. A. (J. Am. Chem. Soc., 1960)

(untitled) - Sheppard, W. A. (J. Am. Chem. Soc., 1962)

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley-VCH, 2004)

Fluorine-Containing Synthons - Winter, R. W.; Dodean, R. A.; Gard, G. L. (SF5-Synthons: Pathways to Organic Derivatives of SF6, 2005)

Current Fluoroorganic Chemistry - Kirsch, P.; Röschenthaler, G.-V. (Functional Compounds Based on Hypervalent Sulfur Fluorides, 2007)

Fluorine in Pharmaceutical and Medicinal Chemistry - Welch, J. T. (Imperial College Press, 2012)

WO Patent - Bowden, R. D.; Greenhall, M. P.; Moilliet, J. S.; Thomson, J. (The preparation of fluorinated organic compounds, 1997)
Chem. Abstr. 1997, 126, 199340.

(untitled) - Bowden, R. D.; Comina, P. J.; Greenhall, M. P.; Kariuki, B. M.; Loveday, A.; Philp, D. (Tetrahedron, 2000)

(untitled) - Chambers, R. D.; Spink, R. C. H. (Chem. Commun., 1999)

(untitled) - Umemoto, T.; Garrick, L. M.; Saito, N. (Beilstein J. Org. Chem., 2012)

(untitled) - Beier, P.; Pastýříková, T.; Vida, N.; Iakobson, G. (Org. Lett., 2011)

(untitled) - Beier, P.; Pastýříková, T.; Iakobson, G. (J. Org. Chem., 2011)

(untitled) - Iakobson, G.; Beier, P. (Beilstein J. Org. Chem., 2012)

(untitled) - Beier, P.; Pastýříková, T. (Tetrahedron Lett., 2011)

(untitled) - Pastýříková, T.; Iakobson, G.; Vida, N.; Pohl, R.; Beier, P. (Eur. J. Org. Chem., 2012)

(untitled) - Vida, N.; Beier, P. (J. Fluorine Chem., 2012)

(untitled) - Altomonte, S.; Zanda, M. (J. Fluorine Chem., 2012)

(untitled) - Wipf, P.; Mo, T.; Geib, S. J.; Caridha, D.; Dow, G. S.; Gerena, L.; Roncal, N.; Milner, E. E. (Org. Biomol. Chem., 2009)

(untitled) - Mo, T.; Mi, X.; Milner, E. E.; Dow, G. S.; Wipf, P. (Tetrahedron Lett., 2010)

(untitled) - Lai, C.-T.; Hong, J.-L. (J. Phys. Chem. B, 2010)

(untitled) - Bose, D. S.; Idress, M.; Jakka, N. M.; Rao, J. V. (J. Comb. Chem., 2010)

(untitled) - Shaabani, A.; Soleimani, E.; Badri, Z. (Monatsh. Chem., 2006)

(untitled) - Zhang, J.; Zhu, D.; Yu, C.; Wan, C.; Wang, Z. (Org. Lett., 2010)

(untitled) - Karnakar, K.; Shankar, J.; Narayna Murthy, S.; Ramesh, K.; Nageswar, Y. V. D. (Synlett, 2011)